Annotation rules for XML schemas with grouped semantic annotations - Campos-Rebelo, Rogério (2019)
To enable the Industrial Internet of Things (IIoT), it is required to ensure Machine-to-Machine communications. Systems/devices often use different communication protocols, standards, and data representation languages, which create interoperability challenges. This paper proposes a set of annotation rules for systems meta-data, to support the translation of data exchanged between heterogeneous systems. These rules must be followed to ensure the validity of systems meta-data (XML Schemas annotated with semantic annotations and group identifiers). The meta-data can then be used as input in tools to analyze data and semantic compatibility and generate translators.